Aspek-Aspek Profesionalisme, Karakteristik Profesionalisme, Watak Kerja Seorang Profesionalisme: Bahasa Indonesia - Much. Machfud Arif; Tsalits Fahmi (MUMTAZ - Education Management and Islamic Studies, 2025)
This paper discusses the characteristics and aspects of professionalism, especially in the context of the teaching profession. Professionalism is defined as attitudes, behaviors, and qualities that demonstrate expertise, integrity, and commitment in carrying out tasks according to professional standards and codes of ethics. Aspects of professionalism include potential, skills, functional abilities, operational, personality, and productivity. Characteristics of professionalism include the desire to achieve perfection, accuracy, perseverance, and work effectiveness, supported by fighting spirit, competence, creativity, and loyalty to tasks and the nation. Professionalism demands experience and habits that form a serious and loyal work attitude, which is very important in improving the quality of work and dedication, especially in the teaching profession as the main pillar of education. This paper also recognizes the shortcomings and expects criticism and suggestions from readers for further development.